2023
DOI: 10.3390/en16124552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coupling Combined Heat and Power Production with District Cooling

Abstract: Over the past decades, combined heat and power production (CHP) has proven itself to be an efficient means of meeting both heat and power demands. However, high efficiency can be achieved with CHP plants when the heat load is sufficient, while lower-priority CHP plants must deal with the excess heat associated with power generation. This excess heat can be used for district cooling with absorption chillers. Although the absorption chiller is an efficient technology for using excess heat for cooling generation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…According to the authors of the cited work, such a system has a chance to achieve net-zero CO 2 emissions. This is confirmed by the results of the analysis carried out in [49] for the technology campus in Tallinn (Estonia). It has been shown that the use of system cooling can result in "1.9 times less primary energy for cooling generation than local cooling".…”
Section: Introductionsupporting
confidence: 66%
“…According to the authors of the cited work, such a system has a chance to achieve net-zero CO 2 emissions. This is confirmed by the results of the analysis carried out in [49] for the technology campus in Tallinn (Estonia). It has been shown that the use of system cooling can result in "1.9 times less primary energy for cooling generation than local cooling".…”
Section: Introductionsupporting
confidence: 66%
“…In recent studies, combined heat and power (CHP) systems have been increasingly investigated in the context of district heating and in combination with other energy systems. One such study, conducted by the authors of [18], provides a comprehensive analysis of the impact of cooling generation in CHP plants using absorption chillers on power generation and primary energy consumption. The research findings suggest that to effectively utilize excess heat from CHP systems and achieve efficient cooling production, the recommended configuration includes an 0.8 MW absorption cooler and 11.6 MW heat pumps.…”
Section: Pv-chp Hybrid Sytemsmentioning
confidence: 99%